The proposed reform of the direct payments' system after 2013 and its impact on the situation of Polish agriculture - Czubak, Wawrzyniec; Poczta, Walenty; Sadowski, Arkadiusz (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2011)
The article presents the results of research launched to define the effects that some of the essential changes in the system of direct payments, proposed by the European Commission, may have for the economic situation of the agricultural sector and for individual groups of farms after 2013. The conducted research has made it possible to establish that the necessity to exclude part of the farmland from cultivation and to destine it for ecological purposes will be that element of the planned changes that is going to produce the most serious effects. The influence of this instrument will be relatively weak in relation to the agricultural sector as a whole but it may contribute to a fall in incomes predicted in accordance with a simulation of their level for 2013, especially in the case of intensive and economically largest farms. The duty to exclude a part of the land from production to be imposed on all farms larger than 3 ha will also contribute to a reduction in the production potential and to the upsetting of spatial order, without producing any major pro-environmental effect. Another of the analyzed elements of reform – capping, which consists in the limitation of payments to the largest farms, will not, however, cause – with the exception of a few very large farms, any serious worsening in the economic situation of these entities owing to the possibility of deducting the cost of labor.
Keywords: direct payments; reform; changes in the incomes of farms